Modelling basic numeracy learning application for children with autism: a pilot study / Muhamad Fairus Kamaruzaman, Harrinni Mohd Noor and Mustaffa Halabi Hj Azahari - Mohd Noor, Harrinni; Hj Azahari, Mustaffa Halabi (Penerbit UiTM (UiTM Press), 2017)
Children with autism have various difficulties in developing cognitive abilities and attaining new knowledge. However, it is essential they obtain a competence approach in order to achieve independence. The state of art has shown that a significant aspiration for children with autism is to become independent. Part of attaining independence includes achieving skills that allow for self-determination and involvement in social activities. Hence, it is essential for every child with autism to acquire basic numeracy skills to enhance their self-determination. With the emergence of assistive learning technology such as smartphones, PDAs, tablets, and laptops with touchscreen features, there are extensive ways to improve the quality of life for children with autism. This study, therefore, aims to explore the basic numeracy skills-based dynamic visual for children with autism that will possibly be of assistance to parents, educators, and facilitators in the development of digital assistive learning tools to meet the requirements of children with autism in learning environments. From the proposed theoretical framework, an application was designed and tested with several children with autism. Based on observations from the experiment, the users showed positive attitudes towards the outcome of the application.